Response to Critics - Schönbaumsfeld, Genia (International journal for the study of skepticism, 2021)
Abstract In this paper I respond to the objections and comments made by Ranalli, Williams, and Moyal-Sharrock, participants in a symposium on my book on scepticism called The Illusion of Doubt.